KONSTRUKSI REALITAS RASISME DALAM FILM THE HELP - Yeka Syamela; Suyanto, " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The Help is a movie with rasicm theme, this movie tell about the life of offspring blacks African-American in America in the past. The purposes of this research are to know and analyse the reality constrution of rasicm on “The Help”and also to know the spectator‟s point of view in seeing this movie.This research uses qualitative method based on Charles Sandrs Peirce Semiotic analysis model and interview technique through Focus Group Discusion (FGD) based on primary data and secondary dta. The technique of data validity uses triangulasi that is comparing the documentasi data tu the result of the research observation.The results of this research found that, rasicm on “The Help” covers fort aspects, those are, racisl prejudice, racial stereotypes, racial discrimonation, and racial violence, which were found by Peirce‟s semiotic analysis model, and the construction of rasicm reality in this film persuades and presents the attitude changing of the audience, especially American people to change the negative view of blacks and accept the coexistence with diffrent races.Keywords : Construction of Reality, Rasicme, Film